Cyclosporiasis Among School Going Children of Kathmandu Valley - Sherchand, Shardulendra Prasad; Joshi, Dev Raj; Adhikari, Nabaraj; Pant, Krishna Prasad; Pun, Ramesh (Nepal Journal of Science and Technology, 2011)
Intestinal parasitic infections among children possess a critical public health issue in Nepal. This study was conducted to determine cyclosporiasis among school going children of Kathmandu valley. A total of 187 collected stool samples were subjected to direct microscopy, formal-ether concentration technique, Sheather’s sucrose floatation technique and modified acid fast staining technique. The incidence of cyclosporiasis, cryptosporidiosis and other intestinal parasitosis was 24.1%, 29.4% and 51.9% respectively. The cyclosporiasis was higher in female (28.4%) without any significance (p=0.190). The cyclosporiasis was found highest in age group 5-8 (25.2%) but statistically insignificant (p=0.895). Cyclosporiasis was higher in symptomatic case (25.6%) but found statistically insignificant (p=0.469). Similarly, cyclosporiasis was higher in school children without following hygienic practice (28.0%) but without any significance (p=0.103). There was significant difference between detection of cyclospora before and after sporulation by modified acid fast staining technique (p<0.001) and highest association was seen between Cyclospora cayetanensis and Cryptosporidium parvum. The outcome of this study revealed that cyclosporiasis remain highly endemic in school children of Kathmandu valley. This suggests proper diagnosis and specific treatment is required to lower the parasitic burden. Key words: Cyclospora cayetanensis; Cryptosporidium parvum; modified acid fast staining technique DOI: 10.3126/njst.v11i0.4145 Nepal Journal of Science and Technology 11 (2010) 193-198